2013
DOI: 10.1155/2013/370938
|View full text |Cite
|
Sign up to set email alerts
|

Development of Oral Sustained Release Rifampicin Loaded Chitosan Nanoparticles by Design of Experiment

Abstract: Objective. The main objective of the present investigation was to develop and optimize oral sustained release Chitosan nanoparticles (CNs) of rifampicin by design of experiment (DOE). Methodology. CNs were prepared by modified emulsion ionic gelation technique. Here, inclusion of hydrophobic drug moiety in the hydrophilic matrix of polymer is applied for rifampicin delivery using CN. The 23 full-factorial design was employed by selecting the independent variables such as Chitosan concentration (X 1), concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(45 citation statements)
references
References 20 publications
2
43
0
Order By: Relevance
“…Despite the weak acidic nature of PEAA which was believed to reduce its dissolution under the 569 acidic conditions of this study (0.1N HCl), PEAA-CS particles exhibited a burst effect, possibly because some 570 of PMZ was attached to the surface of the nanoparticles and released ring the first few hours of the 571 dissolution study as suggested earlier by (Patel, Parikh, & Aboti, 2013). On the other hand, PVP and PEG 572 coated nanoparticles showed the slowest amount of drug release over 24hr.…”
mentioning
confidence: 67%
See 2 more Smart Citations
“…Despite the weak acidic nature of PEAA which was believed to reduce its dissolution under the 569 acidic conditions of this study (0.1N HCl), PEAA-CS particles exhibited a burst effect, possibly because some 570 of PMZ was attached to the surface of the nanoparticles and released ring the first few hours of the 571 dissolution study as suggested earlier by (Patel, Parikh, & Aboti, 2013). On the other hand, PVP and PEG 572 coated nanoparticles showed the slowest amount of drug release over 24hr.…”
mentioning
confidence: 67%
“…The ability of CS to form nano-94 microparticulate systems depends on its ability to form covalent cross-linking between the chitosan chain 95 and the functional cross-linking agent such as polyehtlene glycol (PEG), dicarboxlylic acid or 96 tripolyphosphate. Patel et al (2013) utilised CS to develop a sustained delivery system of Rifampicin. 97…”
Section: Fig 1:-chemical Structure Of Chitosan (A) and Promethazine (mentioning
confidence: 99%
See 1 more Smart Citation
“…Considering a number of reports, this eff ect could be attributed to drug diff usion out of the particles during the size reduction at the high homogenization speeds (Yoncheva et al 2003, Patel et al 2013. Conversely, the drug concentration had a positive eff ect on entrapment effi ciency.…”
Section: Eff Ect Of the Variables On Entrapment Effi Ciencymentioning
confidence: 99%
“…Dialysis bag diffusion technique with minor modifications was employed for in vitro catechin release studies [13]. The study was performed for six concentrations of CATNP, namely, 1, 2, 5, 10, 12, and 15 mg/ml.…”
Section: In Vitro Catechinmentioning
confidence: 99%